Relações entre automonitoria, problemas de comportamento e habilidades sociais na infância - Robalinho, Ivana Gisel Casali (2013)
The literature recognizes the importance of social relationships for the healthy development of children. A good social skills repertoire is crucial for this because it allows one to competently deal with the interpersonal demands. Socially competent children have better prospects for the future, while, in the other hand, deficits on the social skills repertoire are associated with behavior problems and other risk factors for development. Social competence depends on a class of skill that is the basis of all others: self-monitoring. This research, which involved two studies, focused on the relationship between social skills, behavior problems and specific indicators of behaviors which are components of the self-monitoring process as well as the relationships between these variables and socio-demographic variables. In Study there were 220 children, of both genders, who attended the 3rd to the 6th grades of elementary education in public or private schools, as well as their parents / guardians who participated as informants. We used the Brazilian version of the Social Skills Rating System (SSRS-BR) and Brazil Economic Classification Criterion (CCEB). Descriptive and inferential statistics analyses pointed that: (1) the sample had scores consistent with the norm for social skills and behavior problems, and that the internalizing were more frequent, according to the parents / guardians; (2) social skills with greater loadings on predicting behavioral problems were: the Responsibility of (the self-assessed) and Composure and Civility (evaluated by informants), (3) social skills of Kindness were evaluated as the ones with greater social relevance according to parents / guardians; (4) there were significant differences for the repertoire of social skills when we take into account variables such as gender, school year and school type; the socioeconomic status, on the other hand, significantly influenced only internalizing behavior problems. In Study II there was larger sample, 30 children, divided into two groups: 15 children with higher scores on social skills and lower scores of behavior problems and 15 children with opposite repertoire. We used the Structured Situations roadmap, the Interview roadmap as well as the Protocol for the Self-Monitoring Assessment. We carried out descriptive and inferential statistical analysis and we found that: (1) children showed greater ease to Describing their own actions and more difficult to Developing possible alternatives of action, (2) in terms of the specific components of self-monitoring, the group to higher score on social skills and lower behavior problems performed better on Describing the actions of others, Developing possible alternatives of action, Predicting their own feelings, Predicting the reactions of others, Predicting the feelings of others and Reporting, where necessary, changes to the future course of action, (3) girls had significantly higher scores than the boys only for Describing the actions of those with whom they interact. The results suggest the importance of investing in planning interventions aimed at promoting self-monitoring in school-age children as a way of contributing to the socio-emotional development and prevention of behavior problems.